Photoluminescence Study of B‐Trions in MoS2 Monolayers with High Density of Defects. Issue 3 (8th October 2018) - Kaupmees, Reelika; Komsa, Hannu‐Pekka; Krustok, Jüri
Abstract : Photoluminescence spectroscopy has been used to investigate the details of B band emission from single‐layer MoS2 samples grown by chemical vapor deposition. The evolution of the peak shape upon variable excitation power is well described by a combination of exciton and trion contributions, from which B trion binding energy of 18 meV has been extracted. It has been suggested that the absence of accompanying A trion emission in our samples, as well as the enhanced intensity of the B band, can be ascribed to a fast non‐radiative recombination channel arising from the large defect density in our samples. It has been found that band‐selective recombination channels or formation of dark/bright trions are possible microscopic scenarios for our observations. Abstract : Photoluminescence spectra of CVD grown MoS2 monolayer exhibit two predominant bands ( A and B ) corresponding to the optical transitions at the K ‐point in the Brillouin zone. While the A ‐band exhibits only specific excitonic properties, the B ‐band has a double structure. The evolution of the B ‐band shape upon variable excitation power is well described by a combination of exciton and trion contributions, from which B ‐trion binding energy of 18 meV has been extracted.